Disguises of the Invisible: The practice of social invisibility in serial narrative (TEL Tempo, Espaço e Linguagem, 2023)
This article seeks to discuss the representation of social invisibility in the Lupin series, based on the analysis of the disguises chosen by the protagonist to escape, or even go unnoticed by his pursuers. We will depart, as a theoretical basis, from the sociological understanding brought by Stuart Hall (2000) to the identities in the formation of oneself and of the other about oneself; and the principles of symbolic power investigated by Pierre Bourdieu (2001), in addition to other theoretical supports. As a methodology, a descriptive analysis of the narrative was chosen, with a note of its main moments, along with a choice of frames that reproduce the questions to be raised here. We point out, in the final considerations, how the invisibility of the black individual, and also of the elderly, perpetuates layers of a social organization based on the privileges of certain groups to the detriment of others.